Environmental Management - Case Study: Urban and Rural Development in Mozambique - Amade, Ricardo; Brito, Brígida (Revista da UI_IPSantarém, 2023)
The management of the environment presents itself as a valuable tool for the ability to act in the development of different services including as tourism in Mozambique, assuming economic, social, cultural, and political dimensions, including the management of the environment. This set of potential makes it possible to exert a positive influence on society when accompanied by changes in the lives of populations, from the creation of jobs, professional training, health, and other components as a guarantee of human and sustainable development. This interaction contributes to the well-being of individuals and to the reduction of household poverty levels. This study reflects on the strategic focus on environmental management as a support for the Economic and Sustainable Development of Mozambique. The Article comprises institutional strengthening activities at different levels of the Government in the construction and maintenance of urban and rural, infrastructures, highlighting from a small scale, such as: construction and rehabilitation of access roads, drilling of boreholes and construction of small water supply systems, construction of public toilets, construction of drainage ditches and porches in municipal markets, education of citizens in the recycling of garbage and/or solid waste and among other public health care.